Development of Temporal Macrostructure in Life Narratives Across the Lifespan. Issue 2 (17th February 2017) - Köber, Christin; Habermas, Tilmann
Abstract : In Western cultures, life narratives are typically expected to recount the narrator's life from birth to the present. Disparate autobiographical memories need to be integrated into a more or less coherent story, which is facilitated by an overarching temporal macrostructure. The temporal macrostructure consists of elaborated beginnings that contextualize the self in pre-existent family and society, a linear temporal order, and elaborated endings. The present study longitudinally examines the development of temporal macrostructure in life narratives across the lifespan. In this cohort-sequential study, 172 German participants ages 8 to 69 years narrated their lives over the course of 8 years, resulting in up to four life narratives per person. The evidence substantially supports the hypothesis that temporal macrostructure in life narratives emerges in adolescence, with some continuing developmental change throughout adulthood. The evidence also strongly indicates that story structure and life story structure differ in their development.